JARINGAN SOSIAL PERAJIN GERABAH DALAM MEMPERTAHANKAN USAHA di GAMPONG ME MATANG PANYANG ACEH UTARA - Dewi Fatma Dewi; Fauzi Fauzi (Jurnal Sosiologi Dialektika Sosial, 2022)
This study examines the Social Network of Pottery Craftsmen in Maintaining Their Business (Study in Gampong Me Matang Panyang, Tanah Pasir District, North Aceh Regency). This study focuses on the causes of pottery craftsmen to remain as pottery craftsmen, the pottery craftsman business network to distribute pottery production, and the marketing strategies carried out by pottery craftsmen to encourage people's interest in buying pottery. This study uses Putnam's theory of social capital which discusses three things, namely social/business networks, norms, and trust. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques used in this study are observation, interviews, and documentation. The results of this study indicate that the causes of pottery craftsmen persist in Gampong Me Matang Panyang are (a) pottery as a livelihood for the community and permanent work for pottery craftsmen to earn income, (b) pottery is still in demand by buyers, especially toke which accommodates pottery, pottery traders and buyers in the surrounding villages. The business network of pottery craftsmen in distributing pottery production in Gampong Me Matang Panyang is (a) building a business network with pottery traders and traveling traders, and (b) cooperating with toke which accommodates pottery production in marketing pottery to other areas. The marketing strategies of pottery craftsmen in Gampong Me Matang Panyang to encourage buyers' interest are (a) building pottery businesses in other areas that are permanent and located by renting shop houses in urban market areas, and (b) trading pottery around by selling directly to buyers.Penelitian ini mengkaji Jaringan Sosial Perajin Gerabah Dalam Mempertahankan Usahanya (Studi di Gampong Me Matang Panyang Kecamatan Tanah Pasir Kabupaten Aceh Utara). Penelitian ini mengfokuskan pada penyebab perajin gerabah tetap bertahan menjadi perajin gerabah, jaringan bisnis perajin gerabah untuk mendistribusikan produksi gerabah, dan strategi pemasaran yang dilakukan oleh perajin gerabah untuk mendorong minat masyarakat membeli gerabah. Penelitian ini menggunakan teori modal sosial Putnam yang membahas tiga hal yaitu jaringan sosial/bisnis, norma, dan kepercayaan. Metode penelitian yang digunakan dalam penelitian ini yaitu metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa penyebab perajin gerabah tetap bertahan di Gampong Me Matang Panyang adalah (a) gerabah sebagai mata pencaharian masyarakat dan pekerjaan tetap perajin gerabah untuk memperoleh pendapatan, (b) gerabah masih diminati pembeli terutama toke yang menampung gerabah, pedagang gerabah keliling maupun pembeli di gampong sekitarnya. Jaringan bisnis perajin gerabah dalam mendistribusikan produksi gerabah di Gampong Me Matang Panyang adalah (a) membangun jaringan bisnis dengan pedagang gerabah maupun pedagang keliling, dan (b) bekerjasama dengan toke yang menampung produksi gerabah dalam memasarkan gerabah ke daerah lainnya. Strategi pemasaran perajin gerabah di Gampong Me Matang Panyang untuk mendorong minat pembeli adalah (a) membangun usaha gerabah didaerah lain bersifat menetap dan bertempat dengan menyewa ruko di daerah pasar perkotaan, dan (b) berdagang gerabah keliling dengan menjual langsung kepada pembeli.